Characterization of Methicillin-Resistant Staphylococcus aureus, Vancomycin-Resistant Enterococci and Extended-Spectrum Beta-Lactamase-Producing Escherichia coli in Intensive Care Units in Canada: Results of the Canadian National Intensive Care Unit (Can-Icu) Study (2005–2006) - George G Zhanel; Mel DeCorby; Kim A Nichol; Patricia J Baudry; James A Karlowsky; Philippe RS Lagace-Wiens; Melissa McCracken; Michael R Mulvey; Daryl J Hoban; The Canadian Antimicrobial Resistance Alliance (CARA) (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and vancomycin-resistant enterococci (VRE) are important hospital pathogens in Canada and worldwide.